Optimal Short-Sighted Rules - Bourgeois-Gironde, Sacha (Frontiers in Neuroscience, 2012)
The aim of this paper is to assess the relevance of methodological transfers from behavioral ecology to experimental economics with respect to the elicitation of intertemporal preferences. More precisely our discussion will stem from the analysis of Stephens and Anderson’s (2001) seminal article. In their study with blue jays they document that foraging behavior typically implements short sighted choice rules which are beneficial in the long-run. Such long term profitability of short-sighted behavior cannot be evidenced when using a self-control paradigm (one which contrasts in a binary way sooner smaller and later larger payoffs) but becomes apparent when ecological patch-paradigms (replicating economic situations in which the main trade-off consists in staying on a food patch or leaving for another patch) are implemented. We transfer this methodology in view of contrasting foraging strategies and self-control in human intertemporal choices.